2018
DOI: 10.2147/ijn.s155383
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-loaded redox-sensitive nanoparticles based on hyaluronic acid-vitamin E succinate conjugates for improved lung cancer treatment

Abstract: BackgroundLung cancer is the primary cause of cancer-related death worldwide. A redox-sensitive nanocarrier system was developed for tumor-targeted drug delivery and sufficient drug release of the chemotherapeutic agent paclitaxel (PTX) for improved lung cancer treatment.MethodsThe redox-sensitive nanocarrier system constructed from a hyaluronic acid-disulfide-vitamin E succinate (HA-SS-VES, HSV) conjugate was synthesized and PTX was loaded in the delivery system. The physicochemical properties of the HSV nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 32 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Targeted drug delivery with enhanced anti-tumor efficacy Targeted drug delivery system HA oligomer-HPMA copolymer conjugated paclitaxel targeted to CD44-overexpressing ovarian tumors Micellar targeted intracellular delivery of paclitaxel Targeting of human squamous cell carcinomas of the head and neck Intracellular anti-tumor targeting Intracellular anti-tumor drug delivery HA-paclitaxel prodrugs for direct cytosolic delivery and enhanced anti-tumor activity Broad anti-cancer treatment Improved anti-tumor activity and safety delivery of paclitaxel [369] [370]…”
Section: Docetaxelmentioning
confidence: 99%
“…Targeted drug delivery with enhanced anti-tumor efficacy Targeted drug delivery system HA oligomer-HPMA copolymer conjugated paclitaxel targeted to CD44-overexpressing ovarian tumors Micellar targeted intracellular delivery of paclitaxel Targeting of human squamous cell carcinomas of the head and neck Intracellular anti-tumor targeting Intracellular anti-tumor drug delivery HA-paclitaxel prodrugs for direct cytosolic delivery and enhanced anti-tumor activity Broad anti-cancer treatment Improved anti-tumor activity and safety delivery of paclitaxel [369] [370]…”
Section: Docetaxelmentioning
confidence: 99%
“…Nanoparticles (NPs) are vehicles that can prolong drug circulation time, transfer hydrophobic drugs, enhance the accumulation of drugs in tumor tissues through enhanced permeability and retention effect, and reduce normal tissue toxicity. Therefore, various kinds of NPs, including liposomes, micelles, and magnetic NPs, were fabricated to enhance the therapeutic effects of anticancer drugs [7][8][9]. However, inefficient drug release of the traditional micelles at the tumor site restricts the therapeutic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a research study was conducted to explore the effects of Stephania kwangsiensis root tubers on the proliferation and apoptosis of the NCI-H446 cells-a lung adenocarcinoma model. The results demonstrated that corydine has marked cytostatic and proapoptotic effects on human small cell lung cancer [56,57].…”
Section: Lung Cancermentioning
confidence: 94%
“…The PTX-loaded redox-sensitive nanoparticles has shown greater in vitro cytotoxicity and apoptosis-inducing ability against CD44 over-expressed A549 tumor cells in comparison to the redox-insensitive nanoparticles [53]. In an in-vivo study, the PTX-loaded HSV nanoparticles exhibited an enhanced antitumor efficacy in a A549 mouse xenograft model [54].…”
Section: Lung Cancermentioning
confidence: 97%